Epidemic abortions due to Neospora caninum infection in farmed red deer (Cervus elaphus) - Soler, Juan Pablo (2022)
This study describes for the first time an abortion outbreak caused by Neospora caninum in farmed red deer. During a 5-year period, farmed hinds, naturally mated, were regularly ultrasound monitored to detect reproductive losses over their gestation. During the 4 years previous to the outbreak, abortion rates ranged from 4.7 to 8.6% (average 6.5%), and serology for indirect diagnosis of neosporosis and toxoplasmosis was performed. At the fifth year, the abortion rate increased to 25.3%. During this outbreak, three aborted foetuses and their placentas were recovered and submitted to laboratory for etiological diagnosis. Blood samples were collected from the 81 hinds at the end of the gestational period and the seropositivity rate for N. caninum, Toxoplasma gondii, Brucella abortus, bovine viral diarrhoea virus and bovine alphaherpesvirus type 1 was 66.7%, 67.9%, 0.0%, 8.6% and 0.0%, respectively. Neospora caninum-seropositive hinds (OR = 5.7, P = 0.0271) and hinds with high antibody titres to N. caninum (OR = 7.4, P = 0.0130) were more likely to abort than seronegative hinds. In addition, N. caninum seropositivity rate in the aborted hinds was higher (OR = 5.4, P = 0.033) than the non-aborted hinds. No association was found between T. gondii nor BVDV-seropositivity and abortions. Typical protozoal histopathologic findings (necrotizing non suppurative encephalitis, meningitis, myocarditis, hepatitis, among others) were observed in all foetuses. Neospora caninum was immunolabelled by immunohistochemistry in several tissues from two foetuses, and infection was also confirmed in the three foetuses by serology and/or DNA detection. No other abortifacient agent was detected in the foetuses. Their dams showed high N. caninum antibody titres (≥ 6400). Serologic evidence and epidemiological data recorded suggested a point-source of N. caninum infection before the occurrence of the outbreak, probably related with contaminated feedstuff with oocysts. Moreover, the intensive production system with a high stocking rate could be also considered a factor which might have increased the risk of horizontal N. caninum infection in this herd.